The missionary at home: the Church in the towns, 1000–1250 - Brooke, Christopher Nugent Lawrence (Studies in church history, 1970)
The wide span of years which I have boldly claimed in my title is intended to enmesh and hold together for our inspection the first great age of the medieval city, the tenth and eleventh centuries, when the medieval Church first faced the problem of evangelism in growing mercantile communities, and the age when it deployed in the cities and towns of Europe a new army of missionaries in the persons of the friars. The missionary techniques of the friars are familiar and comparatively well documented; the evangelism of the tenth and eleventh centuries is scarcely documented at all. In recent years the dramatic nature of urban history in this early period has been becoming increasingly apparent; and it was in the conviction that the Church’s hand in it could not wholly escape detection that I chose the title for this lecture. Many aspects of this problem have been traced with the closest care; but I justify the breadth and cloudiness of my theme by a conviction that it has rarely been looked at quite from this point of view.